Cisplatin-Based Chemotherapy Eligibility: Discrepancy Between Serum Creatinine Level and Glomerular Filtration Rate - Moghadam, Shiva; Novin, Kambiz; Mortazavi, Nafiseh; Hosseini Kamal, Farnaz; Khoshbakht Ahmadi, Helaleh; Ameri, Ahamd (Reports of Radiotherapy and Oncology, 2015)
Background: Serum creatinine level is frequently used as a measure for renal function assessment. However, there are some situations in which patients may suffer significant renal impairment but serum creatinine levels remain within normal ranges. Objectives: We conducted this study to evaluate the discrepancy between serum creatinine (SCr) level and glomerular filtration rate (GFR) in determining the eligibility for cisplatin-based chemotherapy among cancer patients. Patients and Methods: A total of 198 cancer patients had received cisplatin-based chemotherapy at Jorjani Cancer Center, Emam Hossein Hospital, Tehran, Iran were retrospectively investigated. The discordance between SCr level and calculated GFR by Cockcroft-Gault equation was analyzed. Results: 130 patients (66%) were men and 68 (34%) were women with mean age of 54.5 years. Squamous cell carcinoma (SCC) and head and neck were the most common primary tumor histology and site respectively. Of 165 patients with available data to calculate eGFR, 45 (27.3%) had normal kidney function based solely on SCr levels, but their GFR was less than 60 mL/min (renal dysfunction). The discordance between SCr and GC calculated GFR values were most pronounced in the older age, transitional cell carcinoma histology and bladder primary site. Conclusions: This study shows that SCr level alone may not be a reliable measure of normal kidney function to determine eligibility for cisplatine-based chemotherapy.